2019
DOI: 10.3390/jmse7030055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Underwater Bar Location on Cross-Shore Sediment Transport in the Coastal Zone

Abstract: The effect of the underwater bar position on a sandy beach profile was studied on a timescale of one storm, using the XBeach numerical model. The largest shoreline regress occurred in the first hour of storm. For the chosen wave regime an underwater profile close to the theoretical Dean’s equilibrium profile is formed after 6 h. The position of the underwater bar affects the shoreline retreat rate. The lowest shore retreat occurs when the bar crest is located at a distance equal to 0.70–0.82 of the deep-water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…They also underlined the importance of a modeling-monitoring feedback system. Kuznetsova and Saprykina [11] analyzed how the beach profile is influenced by the location of underwater bars. They performed this study by using a numerical model with attention paid to the time scale of a given storm.…”
Section: Papers Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also underlined the importance of a modeling-monitoring feedback system. Kuznetsova and Saprykina [11] analyzed how the beach profile is influenced by the location of underwater bars. They performed this study by using a numerical model with attention paid to the time scale of a given storm.…”
Section: Papers Detailsmentioning
confidence: 99%
“…The issue collected five papers that cover different aspects of coastal and ocean engineering, chemical oceanography, geology, and geomorphology using different approaches and instruments. Some of the studies used numerical models [10,11], others acquired and analyzed field data regarding chemical [12] or geomorphological aspects of the ocean [13] while Lisi et al [14] suggested a mathematical modeling framework to analyze the effects of sediment handling operations.…”
Section: Introductionmentioning
confidence: 99%
“…1) represent an important morphological feature that has implications for human activities in coastal zones (e.g., tourism and surfing) as well as for coastal protection against coastal erosion (Kuang et al 2019;Poate 2011). Sandbars dissipate wave energy through depth-induced wave breaking and reduce wave period through nonlinear dispersive wave transformation in the surf zone (Cohn et al 2014;Kuznetsova and Saprykina 2019;Mulligan et al 2019). Therefore, they influence cross-shore sediment transport processes, affect the shoreline position, and mitigate coastal erosion (Eichentopf et al 2019; Vidal-Ruiz and de Alegria-Arzaburu 2019; Xie et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they influence cross-shore sediment transport processes, affect the shoreline position, and mitigate coastal erosion (Eichentopf et al 2019; Vidal-Ruiz and de Alegria-Arzaburu 2019; Xie et al 2017). Moreover, sandbars reduce the overtopping rates over coastal structures during storm events (Cohn and Ruggiero 2016;Kuznetsova and Saprykina 2019;van der Meer et al 2018;Rutten et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The area between the shoreline and the breaking wave became an area where the dynamic interaction between the water current and the sediment material are occurred. Moving water carried material from one place to another and results in eroding the sediment and then settles it somewhere that will cause the dropping of shoreline (Flemming, Harff, Moura, Burgess, & Bailey, 2017;Kuznetsova & Saprykina, 2019; Vargas-T, Uribe-P, Ríos-R, & Castellanos-A, 2016; Wahyudi, Harijanto, & Suntoyo, 2009). The worst condition was happened when the heavy rain falls which caused flood everywhere.…”
Section: Introductionmentioning
confidence: 99%